Requirements engineering : 26th International Working Conference, REFSQ 2020, Pisa, Italy, March 24-27, 2020, Proceedings /: 26th International Working Conference, REFSQ 2020, Pisa, Italy, March 24-27, 2020, Proceedings. (2020) - Unknown
No abstract available